IMPLEMENTASI KEAMANAN PESAN TEKS MENGGUNAKAN KRIPTOGRAFI ALGORITMA RSA DENGAN METODE WATERFALL BERBASIS JAVA - Rudi Firmansyah; Angga Aditya Permana (Joutica, 2019)
Current technological advances allow users to exchange data and information from one place to another via the internet. The data and information are sometimes important and need to be kept confidential from irresponsible people who can disseminate or change the original data and information. The risk of such threats can be reduced by converting data and information into confidential messages. The author uses RSA cryptography (Rivest Shamir Adleman) technique in converting the original text of the message into secret text. The author will use the JAVA programming language to convert the original text into a number with blocks, then the text message will be changed with the key that was created first. The results of message encryption are expected to be able to secure data and information, because in RSA cryptography there has been no way to decrypt messages other than by using a secret key. The system design method used is the waterfall method.